2005
DOI: 10.1111/j.1600-079x.2005.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin synthesis and melatonin‐membrane receptor (MT1) expression during rat thymus development: role of the pineal gland

Abstract: To gain insight into the relationship between thymus and pineal gland during rat development, the melatonin content as well as the activity and expression of the two key enzymes for melatonin biosynthesis, i.e. N-acetyltransferase (NAT) and hydroxyindole-O-methyltransferase (HIOMT), were studied in the thymus at fetal and postnatal stages. Moreover, melatonin-membrane receptor (MT1) expression was also analyzed. We found both the expression and activity of thymic NAT and HIOMT at 18 days of fetal life. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 41 publications
(48 reference statements)
3
37
0
2
Order By: Relevance
“…Presence of melatonin receptors in thymus completes the evidence of this relationship [44 -46]. Recently, our group has described an endogenous melatonin biosynthesis in rat thymus during development [47]. In the present work, we probe deeper into melatonin production in thymus of adult rats, carrying out additional studies, as well as demonstrating, for the first time, a melatonin synthesis in thymus of humans.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…Presence of melatonin receptors in thymus completes the evidence of this relationship [44 -46]. Recently, our group has described an endogenous melatonin biosynthesis in rat thymus during development [47]. In the present work, we probe deeper into melatonin production in thymus of adult rats, carrying out additional studies, as well as demonstrating, for the first time, a melatonin synthesis in thymus of humans.…”
Section: Introductionsupporting
confidence: 50%
“…Our findings, although a bloodstream melatonin retention cannot completely be ruled out, demonstrate an endogenous biosynthesis in rat thymus, as the AA-NAT and HIOMT mRNAs are expressed and give rise to active enzymes, and thymocytes in culture exhibit high levels of melatonin. Moreover, a recent study of our group showed that pinealectomized rats have a clearly increased thymic melatonin content [47], evidencing an endogenous synthesis, and suggesting that either pineal melatonin could be inhibiting thymic synthesis of melatonin and/or, when pinealsynthesized melatonin is absent, the thymus could show a compensatory rise in melatonin production. Experiments in humans showed a high level of melatonin in thymus homogenate (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of pineal to thymus could be done by pineal peptides [127] or melatonin. It seems likely a functional unity of pineal and thymus involution [79,124,128]. The functional unity is also supported by human experiments, when durable combined treatment with pineal and thymus peptides prolonged the lifespan [129].…”
Section: Discussionmentioning
confidence: 84%
“…The mRNA levels are significantly (* P < 0.05) decreased after melatonin treatment. (Jimenez et al, 2005) and the circadian variation of melatonin content in the pineal gland appears during the 3rd week of extrauterine life (Velazquez et al, 1992). Ultrastuctural observations in the rat pineal gland showed that the pinealocytes adopted an adult morphological appearance around 20 days of age when the circadian melatonin rhythm appeared (Blazquez et al, 1989).…”
Section: Discussionmentioning
confidence: 97%